Evaluating Methods in Arabic Written Expression: Perspectives of Teachers in Al-Dhahira Governorate, Oman - Alkalbani, Awadh; Alazri, Saif (Journal of Arabic Language Studies and Teaching, 2023)
This study investigates the utilization of methods for evaluating written expression from the perspective of Arabic language teachers in Al-Dhahira Governorate, Sultanate of Oman. The population of the study consisted of 345 male and female Arabic language teachers in Al-Dhahira Governorate, with a randomly selected sample of 127 teachers. The study utilized a descriptive methodology and a questionnaire comprising 17 items. The findings indicate a moderate overall degree of usage of methods for evaluating written expression among Arabic teachers in Al-Dhahira Governorate. There were no statistically significant differences, at a significance level of α=0.05, in the utilization of methods based on gender, except for the method of "direct individual correction," which was favored by males. Furthermore, there were no statistically significant differences, at a significance level of α=0.05, in the utilization of methods based on experience across all included methods, ranging from items 1 to 10 and item 11 onwards.